Elite Byzantine Kinship, ca. 950-1204 : Blood, Reputation, and the Genos - Leidholm, Nathan (Nathan Paul) (Beyond medieval Europe., 2019)
This study explores the role and function of the Byzantine aristocratic family group, or genos, as a distinct social entity, particularly its political and cultural role, as it appears in a variety of sources in the tenth through twelfth centuries. While the genos has served as a central component of many historical arguments attempting to explain the changes occurring in this period, no scholar has yet produced a study focused on the genos as a social unit, and even the concept's basic definition remains unclear. At the same time, historians of Late Antiquity, Medieval Europe, and Byzantium have all struggled to find meaningful ways to analyze and interpret kinship structures beyond the household or nuclear family. This work seeks to ameliorate these shortcomings and, in so doing, addresses aspects of cultural, social, and political change in Byzantium through the lens of kinship.